2015
DOI: 10.1513/annalsats.201501-039oc
|View full text |Cite
|
Sign up to set email alerts
|

Communication Skills Training Curriculum for Pulmonary and Critical Care Fellows

Abstract: A structured curriculum that includes abundant opportunities for fellows to practice and receive feedback using a behavioral checklist during their ICU rotations helps to develop physicians with advanced communication skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
74
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 24 publications
0
74
0
1
Order By: Relevance
“…Multiple studies have shown that pediatric intensivists often lack the appropriate skills to conduct these conversations sensitively and adeptly (1, 6, 14, 15). Pediatric critical care physicians (faculty as well as trainees) themselves often feel unprepared to have these difficult and emotion-laden conversations (16, 17). …”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that pediatric intensivists often lack the appropriate skills to conduct these conversations sensitively and adeptly (1, 6, 14, 15). Pediatric critical care physicians (faculty as well as trainees) themselves often feel unprepared to have these difficult and emotion-laden conversations (16, 17). …”
Section: Discussionmentioning
confidence: 99%
“…Programs like IMPACT-ICU could complement training developed for other ICU clinicians. [41][42][43] Some of our sites have expanded the IMPACT-ICU program to include participants from other disciplines. We hope that training of ICU clinicians, in conjunction with integration of palliative care processes into routine practice, 44 will influence aspects of palliative care that did not improve with our program, such as identification of uncontrolled symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In this month's issue of AnnalsATS, there appear two important reports of programs designed to teach critical care fellows to conduct effective and supportive ICU family conferences (10,11). Both reports describe the development and implementation of a formal program for teaching this important skill set, although they apply somewhat different approaches.…”
mentioning
confidence: 99%
“…Both reports describe the development and implementation of a formal program for teaching this important skill set, although they apply somewhat different approaches. Both of these programs also showed improved communication ratings, as assessed by a third-party rater: either a faculty member teaching the course, who could not be blinded to whether fellows had received the training (10), or independent clinical psychologists who were blinded to pre-versus posttraining (11). 520-525) uses a formal family conference checklist as a teaching guide to provide formative feedback to fellows about their performance during actual family conferences in the ICU (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation